Conflicts and protests of Argentinean nursing during the covid-19 pandemic - Ramacciotti, Karina (Casa de Oswaldo Cruz, Fundação Oswaldo Cruz, 2023)
Fil: Ramacciotti, Karina. Universidad Nacional de Quilmes. Departamento de Ciencias Sociales; Argentina.